Integrative multiomics analysis reveals association of gut microbiota and its metabolites with susceptibility to keloids - Li, Dang; Li, Minghao; Gao, Hangqi; Hu, Kailun; Xie, Rongrong; Fan, Jing; Huang, Mingquan; Liao, Chengxin; Han, Chang; Guo, Zhihui; Chen, Xiaosong; Li, Ming (Frontiers in Microbiology, 2024)
Keloid scarring is a fibroproliferative disease of the skin, which can significantly impact one’s quality of life through cosmetic concerns, physical discomfort (itchy; painful), restricted movement, and psychological distress. Owing to the poorly understood pathogenesis of keloids and their high recurrence rate, the efficacy of keloid treatment remains unsatisfactory, particularly in patients susceptible to multiple keloids. We conducted fecal metagenomic analyzes and both untargeted and targeted plasma metabolomics in patients with multiple keloids (MK, n = 56) and controls with normal scars (NS, n = 60); tissue-untargeted metabolomics (MK, n = 35; NS, n = 32), tissue-targeted metabolomics (MK, n = 41; NS, n = 36), and single-cell sequencing analyzes (GSE163973). Differences in the gut microbiota composition, plasma metabolites, and tissue metabolites were observed between the MK and NS groups; the core gut microbiota, Oxalobacter formigenes, Bacteroides plebeius, and Parabacteroides distasonis, were identified via the gut microbiome co-occurrence network. Single-cell data helped clarify the specific cells affected by plasma metabolites. An area under the curve analysis using a random forest model based on fecal metagenomics, plasma metabolomics, and tissue metabolomics revealed that gut bacteria, plasma, and tissue metabolites were effective in distinguishing between MK and NS groups. Decreased Bacteroides plebeius could lower uracil levels, altering systemic lipid metabolism, which may change the metabolic phenotype of secretory reticular fibroblasts in wounds, potentially leading to MK. These findings may open new avenues for understanding the multifactorial nature of keloid formation from the gut-skin axis and highlight the potential for novel therapeutic strategies targeting keloid lesions and the underlying systemic imbalances affected by the gut microbiome.